Diseño y construcción de una cámara automatizada de germinación de cereales para la Facultad de Ciencias Agropecuarias y Recursos Naturales de la Universidad Técnica de Cotopaxi. - Salazar Vargas, Oswaldo de Jesús (2018)
The Climatic and atmospheric changes that are occurring worldwide, have mitigated the crops that farmers perform through specific dates in the year, these are affected until cause the entire loss of crops mainly by frost and excessive rain or heat. Cereals are the most nutritious food consumed by humanity, and the technification of their cultivation is very important for agricultural sectors around the world. That is why science and technology have provided the need of create artificially climatic conditions in germination chambers, promoting the ease of growing cereals or other types of natural food at any time of year. Thus, technology gives the farmer greater economic income and consumers the feasibility of having not shortage of products. The present Research Project designed, built and implemented an automated chamber of germination of cereals for the Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi; the chamber allows improving the germination of cereal seeds, achieving a more uniform germination in the trays where the seeds are planted. At the same time the chamber achieves a homogeneous germination achieving the highest number of seeds germinated per tray, of 15 % this is due to the automated control of temperature and humidity, as well as the construction structure of the chamber; lighting is also a preponderant factor, the colors yellow, white and blue located in each cubicle for each tray of the chamber allow the recognition of the effects which produced the tonicity in the germinated seeds. The control and monitoring of temperature and humidity will be automated to reduce germination time.